P-020 Non-Ischemic Cerebral Enhancing (NICE) Lesions Secondary to Endovascular Aneurysm Therapy: Nickel Allergy or Foreign Body Reaction? Reports of Two Cases and Review of the Literature. (29th July 2016) - Shotar, E; Law-Ye, B; Di Maria, F; Baronnet-Chauvet, F; Zeidan, S; Psimaras, D; Bielle, F; Pecquet, C; Navarro, S; Rosso, C; Cohen, F; Chiras, J; et al.
Abstract : Delayed onset of non-ischemic cerebral enhancing lesions is a rare complication of intracranial aneurysms' endovascular therapy (EVT). This complication has been attributed either to foreign body emboli and subsequent granulomatous reaction or cerebral hypersensitivity and nickel allergy. After retrospective review of all patients managed by EVT at our Institution from January 1st 2012 to December 31st 2014, 2 out of 374 patients (0.5%) with such a complication were identified. Patient # 1 developed non-ischemic cerebral enhancing (NICE) lesions 1 month after balloon assisted coiling of a ruptured anterior communicating artery aneurysm. Patient # 2 developed NICE lesions 12 months (the longest delay reported to date for such complication) after the treatment of a right carotidophthalmic aneurysm by loose coiling and flow diversion. Skin patch testing was performed with all endovascular devices used in the 2 patients and with the European baseline series, including nickel. Patient # 2 demonstrated nickel skin reactivity but none of the 2 patients presented allergic reaction to the devices used during interventions. Based on our observations and review of the literature, we hypothesize that delayed non-ischemic cerebral enhancing lesions after EVT are more likely related to foreign body emboli rather than nickel allergy. Disclosures: E. Shotar: None. B. Law-Ye: None. F. Di Maria: None. F. Baronnet-Chauvet: None. S. Zeidan: None. D. Psimaras: None. F. Bielle: None. C. Pecquet: None. S. Navarro: None. C. Rosso: None. F. Cohen: None. J. Chiras: None. N. Sourour: 2; C; Covidien. F. Clarençon: 2; C; Covidien, Codman.